The Haemophilus influenzae hFbpABC Fe(3+) Transporter: Analysis of the Membrane Permease and Development of a Gallium-Based Screen for Mutants - Anderson, Damon S. (American Society for Microbiology, 2007)
The obligate human pathogen Haemophilus influenzae utilizes a siderophore-independent (free) Fe(3+) transport system to obtain this essential element from the host iron-binding protein transferrin. The hFbpABC transporter is a binding protein-dependent ABC transporter that functions to shuttle (free) Fe(3+) through the periplasm and across the inner membrane of H. influenzae. This investigation focuses on the structure and function of the hFbpB membrane permease component of the transporter, a protein that has eluded prior characterization. Based on multiple-sequence alignments between permease orthologs, a series of site-directed mutations targeted at residues within the two conserved permease motifs were generated. The hFbpABC transporter was expressed in a siderophore-deficient Escherichia coli background, and effects of mutations were analyzed using growth rescue and radiolabeled (55)Fe(3+) transport assays. Results demonstrate that mutation of the invariant glycine (G418A) within motif 2 led to attenuated transport activity, while mutation of the invariant glycine (G155A/V/E) within motif 1 had no discernible effect on activity. Individual mutations of well-conserved leucines (L154D and L417D) led to attenuated and null transport activities, respectively. As a complement to site-directed methods, a mutant screen based on resistance to the toxic iron analog gallium, an hFbpABC inhibitor, was devised. The screen led to the identification of several significant hFbpB mutations; V497I, I174F, and S475I led to null transport activities, while S146Y resulted in attenuated activity. Significant residues were mapped to a topological model of the hFbpB permease, and the implications of mutations are discussed in light of structural and functional data from related ABC transporters.